The Effect of Makassar-Bugis Myths and Traditions in the Application of English Teaching Strategies in Some Universities in South Sulawesi - Sukmawaty; Nasmilah; Nadirah Mahaseng; Marleiny Radjuni (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
Developing human resource and its institution on the basis of indigenous knowledge and wisdom is the theme where this study is embedded. It is a scientific contribution to the development of tertiary education system in which English is offered in all levels and in all scientific areas. This research is based on the fact that English as a foreign language is considered important even though it does not attract many people's interests due to many different factors. The most dominant factors are certainly both teachers and learners of the English as a foreign language (EFL) themselves. This study investigates the effect of myth and tradition of Bugis-Makassar on the teaching strategies of the EFL teachers and the learning strategies of the EFL learners in several universities in South Sulawesi Province. It aims to comprehend the impact of the local culture on the learning process applied by teachers and students. Based on both qualitative and quantitative methods, it is found that three significant categories are underlying the culture - “faith”, “norm”, and “value” inherent in local myth and tradition of Bugis-Makassar value on the preference strategies in foreign language learning. The statistical measurement shows that “value” is the most influential aspect among the others. In addition, the three other categories; ‘Knowledge’, ‘Skill’, and ‘Action’ are of affecting methods from local myth and tradition. Deep understanding on the influence of both myth and tradition, as part of culture society towards students’ learning strategies as well as teachers’ strategies, would be meaningful inputs for adjusting the designed and adapted materials in achieving the objective goals of learning